Application of the amplitude-frequency formulation to a nonlinear vibration system typified by a mass attached to a stretched wire - Akbarzade, M.; Farshidianfar, A. (Прикладная механика, 2014)
The He’s Amplitude-Frequency Formulation is applied to study the periodic solutions of a strongly nonlinear system. This system corresponds to the motion of a mass attached to a stretched wire. The usefulness and effectiveness of the proposed technique is illustrated. The results are compared with exact solutions and those obtained by the harmonic balance show a good accuracy. Approximate frequencies are valid for the complete range of vibration amplitudes. Excellent ag